Cell-Free Fermentation Broth of Bacillus velezensis Strain S3-1 Improves Pak Choi Nutritional Quality and Changes the Bacterial Community Structure of the Rhizosphere Soil - Lu, Kaiheng; Jin, Qing; Lin, Yibo; Lu, Wenwei; Li, Songshuo; Zhou, Chenhao; Jin, Jieren; Jiang, Qiuyan; Ling, Lichen; Xiao, Ming (Frontiers in Microbiology, 2020)
Bacillus velezensis is a plant growth-promoting rhizobacteria (PGPR) that has long been proven to improve the growth of plants and it has been widely used in agriculture. However, in many reports we observed that during the application of bacterial fluids, it appeared that the effect of the cell-free fermentation broth was ignored. The purpose of this study is to compare the effect of the no inoculation treatment (CK), B. velezensis strain S3-1fermentation broth treatment (S), and cell-free fermentation broth treatment (CFB) in the pak choi, soil bacterial community structure, soil enzyme activity, and field soil properties. The results have shown that compared to the inoculation fermentation broth treatment and the no-inoculation treatment, the inoculation of the cell-free fermentation broth treatment can significantly enhance the soluble protein, soluble solids, and ascorbic acid of pak choi. At the same time, it significantly increased the relative abundance of Acidobacteria in the soil, it enhanced the activity of invertase and amylase in the soil, it increased the total phosphorus content and EC (Electrical Conductivity) in the soil, and we observed that the genes related to the C and N soil metabolism were up-regulated, which had been predicted by PICRUSt. Overall, we observed that the inoculation with the CFB treatment had a better effect than the CK treatment and S treatment. This study provides new insights for the application of microbial fertilizers in agricultural production.